Strategi Ketahanan Pangan di Kabupaten Bintan Tahun 2023 - Muhammad Pikri; Yudhanto Satyagraha Adiputra; Eki Darmawan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Food security is a condition of food fulfillment for the entire community. The phenomenon of the problem that occurs in this study is the imbalance between the food needs of the Bintan community and local production. Over the past four years from 2019 to 2022, the production of local food needs from various commodities such as rice, vegetables, fruits, and so on has experienced a significant decline in production. This condition certainly triggers concerns regarding the ability of the Regional Government of Bintan Regency to maintain food security and meet the needs of the community. This research aims to formulate a food security strategy in Bintan Regency. This research uses Koteen's theory which consists of four strategy indicators, namely Organizational Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy. This research uses a qualitative approach method with data collection through interviews and documentation. The results show that the vision and mission of regional apparatus organizations are aligned with the district's vision to improve food security. Programs are focused on increasing food production and price stability. Resource support in the form of budget and facilities is important for program success. Institutional strategies emphasize SOPs, monitoring, divisional coordination and employee training to improve program effectiveness. The findings indicate the importance of inter-organizational synergy and resource strengthening in maintaining food security.